THE URGENCY OF AN EXTERNAL OVERSIGHT INSTITUTION ON THE LEGAL PRODUCTS OF THE PEOPLE'S CONSULTATIVE ASSEMBLY (MPR) - Rofila; Yudi Widagdo Harimurti; Nurus Zaman (Universitas Serang Raya, 2025)
The People's Consultative Assembly is a State Institution regulated in the 1945 Constitution of the Republic of Indonesia, has the authority to determine and amend the 1945 Constitution of the Republic of Indonesia, appoint and dismiss the President and Vice President, is a very large authority in running the wheels of government, there is a decree of the People's Consultative Assembly No. MPR No XI / MPR / 1998 concerning State Administrators who are clean and free from Corruption, Collusion, and Nepotism, this decree invites public polemic because it contains efforts to eradicate KKN must be firmly against anyone who is wrong including President Soeharto while still paying attention to the principle of presumption of innocence and human rights, so that a conflict of interest arises in it, until now there is no external supervisory institution but an Internal supervisor, especially in legal products issued by the MPR, while great power tends to abuse power, the purpose of this study 1) to determine the position of the People's Consultative Assembly in the administration of the State in Indonesia 2) to determine the formulation of an external supervisory institution in the legal products of the People's Consultative Assembly People's Consultative Assembly, the research method used in this research is a type of normative research (Normative Legal Research), with a conceptual approach (conceptual approach), and a statute approach (statute approach), the results of this research are : 1) The position of the People's Consultative Assembly in the Indonesian constitutional system is equal to other state institutions such as the DPR, DPD, KY, MA, MK, and so on, the difference lies in the scope of power or authority held by the People's Consultative Assembly and state institutions whose members consist of the DPR and DPD which should be supervised. 2) The urgency of an External Supervisory Institution to the People's Consultative Assembly (MPR) There are several fundamental reasons: The authority held by the MPR can change and determine the 1945 Constitution of the Republic of Indonesia, can appoint and dismiss the President and Vice President, and there has been a conflict of interest in the MPR Decree Number XI/MPR/1998 concerning State Administrators who are clean and free from Corruption, Collusion, and Nepotism, so the formulation of the MPR State institution is that the Constitutional Court is the right institution to carry out external supervision of the MPR's legal products by conducting a Judicial Review because the MPR's strictness is certain regarding the provisions for changing and determining the 1945 Constitution of the Republic of Indonesia. The purpose of this reformulation is to minimize the occurrence of abuse of authority, conflict of interest, which can harm the community and as a form of responsibility for the authority held by the MPR.